PKM for Making Liquid Organic Fertilizer (POC) Based on Household Waste for Teachers in Polewali Mandar Regency to Support the Realization of Adiwiyata Schools - Arlinda Puspita Sari; Nurmuliayanti Muis; Ramlah Ramlah; Baso Manguntungi; Muhammad Rajib (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Garbage is a big problem that is being faced by the government and the people of Polewali Mandar. The unavailability of landfills and waste processing sites causes people to throw their garbage in any place. This causes environmental pollution due to the stench of garbage and reduced beauty and environmental health. The team from the Biology Education Study Program in collaboration with the Komunitas Guru Penggerak provided training for teachers to be able process waste mainly from household waste into liquid organic fertilizer (LOF). Thus, it can help the government reduce waste problems while producing a useful product, namely LOF. The fertilizer produced can be used to help the growth of plants that are cultivated in the school environment. Teachers can realize Adiwiyata schools, namely schools that are clean and free of waste as well as schools that are healthy and beautiful by various types of plants. The results of the service activities showed that most of the participants agreed that this training activity was in accordance with the theme, the resource persons had good quality as indicated by the material presented and the ability to answer questions. Participants also agreed that this training provided skills strengthening for teachers to process waste into LOF.